Tuberculosis and Silicosis: an insightful perspective - Shally Pandit; Sudatta Chandan; Braja S. Barik; Tahziba Hussain; Sanghamitra Pati (Egyptian Journal of Chest Disease and Tuberculosis)
Tuberculosis (TB) is the most ubiquitous disease related to Silicosis in medium and low-income nations. The government of India has set a target to eliminate TB by 2025, while the International Labor Organization and the WHO aim to eradicate Silicosis from developing countries by 2030. However, the co-existence of Silicosis and TB poses a challenge to achieving these goals. Silica, specifically crystalline silica, is a hazardous mineral found in industries such as ceramics and construction. Silicosis severity is directly related to the augmentation of TB, and silica-exposed individuals, such as miners or sandblasters, have a higher risk of developing TB. Studies have shown that silica exposure increases the likelihood of pulmonary and extrapulmonary TB. The prevalence of Silicosis-TB varies in different regions, but there is a clear association between Silicosis and an increased risk of TB. A comprehensive overview of Silicosis and TB, focused on how Silicosis creates an environment conducive to TB infection, is given in this review article. It explores the impact of Silicosis on different immune cells, lymph nodes, and the lungs; this is specifically elaborated in the context of TB. Additionally, the article provides the diagnosis of Silicosis-associated TB and available treatment options.